Induksi Pematangan Gonad Ikan Lele (Clarias sp.) Menggunakan Oodev dengan Teknik Penyuntikan - Gloria Ika Satriani; Kartina Kartina; Anjelina Mariani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Catfish (Clarias sp.) is a freshwater fish species with high economic potential. One of the most important aspects of catfish aquaculture is hatchery technology. This process involves several critical stages, including broodstock selection, which applies breeding programs and phenotypic analysis to select broodstock with superior characteristics. Hormonal stimulation is also an essential method, in which broodstock are injected with hormones to accelerate gonadal maturation, using both natural and synthetic hormones. However, challenges in the spawning process remain, such as determining the appropriate hormone dosage and timing, as well as maintaining broodstock health. Environmental factors, including temperature, pH, and water quality, also influence spawning success and the quality of produced larvae. In addition, feed management and stocking density must be carefully controlled to support larval growth and survival. To increase the production of catfish seed, research and development of effective hatchery techniques are essential. This study aimed to improve the success and efficiency of OODEV hormone application through intramuscular injections at a dose of 0.5 mg per broodstock body weight, administered once at intervals of 3 days prior to spawning, in order to optimize fertilization rate (FR), hatching rate (HR), and survival rate (SR) of superior catfish larvae. The results showed that OODEV hormone administration influenced the reproductive process of catfish larvae. The use of OODEV hormone has potential to be applied in catfish aquaculture as an alternative method to enhance larval reproductive success.